Incorporating biophysical ecology into high-resolution restoration targets: Insect pollinator habitat suitability models - Tomlinson, Sean; Webber, B.; Bradshaw, S.; Dixon, Kingsley; Renton, M. (Blackwell Science Inc., 2017)
Species distribution models can be informative of the biodiversity impacts of changing environments at global, national, and regional scales, but are often constrained in their resolution to extents not relevant to individual, intensive ecological management programs. We constructed a high-resolution topoclimatic model of spring and summer temperatures across a 152km 2 restoration area on the Swan Coastal Plain, Western Australia, and used it to project energetic expenditure and habitat suitability estimates for four major hymenopteran pollinators. For all species, the most heavily modified landscapes were the least suitable, but only for one species, Zapsilothynnus nigripes, was there evidence that the upper thermal tolerance threshold was exceeded broadly. However, at the higher environmental temperatures that we modeled, some species would need to forage up to 10 times their own body mass every hour to meet their energetic requirements. It seems unlikely that the nutritional requirements of most insect pollinators operating at these higher metabolic rates could be met in an impoverished restoration ecosystem, although resource availability remains to be quantified in these habitats. Hence, to increase the likelihood of restoration success by restoring insect pollination networks, nutritional resources may need to be increased during restoration. Accounting for the way that thermoenergetic requirements shape ecological interactions better positions management trajectories aimed at restoring and maintaining key insect pollinators in "novel" ecosystems.